Agronomic and morphological characteristics of two rice genotypes plant in open land and under two years of sengon (Paraserianthes falcataria) - DULBARI DULBARI; ZAINAL MUTAQIN; HERY SUTRISNO; NI SILUH PUTU NURYANTI; YURIANSYAH YURIANSYAH; DENNY SUDRAJAT; DESTIEKA AHYUNI; HIDAYAT SAPUTRA; LINA BUDIARTI; PRIYADI PRIYADI; FAJAR ROCHMAN; RIZKY RAHMADI; MUHAMMAD ALAM FIRMANSYAH; SAIJO SAIJO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Dulbari, Mutaqin Z, Sutrisno H, Nuryanti NSP, Yuriansyah, Sudrajat D, Ahyuni D, Saputra H, Budiarti L, Priyadi, Rochman F, Rahmadi R, Firmansyah MA, Saijo. 2023. Agronomic and morphological characteristics of two rice genotypes plant in open land and under two years of sengon (Paraserianthes falcataria). Biodiversitas 24: 4927-4933. The increase in population is the biggest challenge for the agricultural sector in providing food needs. The main problem in increasing food production in Indonesia is the limited agricultural land. There is a need to explore alternative land options to address this issue and enhance production capacity, specifically for rice at the national level. One of the potential solutions is to use land currently occupied by plantation crops and forests that can be managed through agroforestry. Sengon (Paraserianthes falcataria (L) I.C.Nielsen) is a forestry plant that offers a comparative advantage for investigation in agroforestry systems due to its relatively open canopy cover and classification as a legume. Therefore, this research aimed to determine the response of the morphological and agronomic characters of two rice genotypes planted in open land under 2-year-old sengon stands. The experiment was conducted from October 2017 to March 2018 in the Sengon community forest of Cikarawang, Bogor, with coordinates 06° 33.061' S and 106° 43.987' E. The results showed that two rice genotypes grown under one-year-old sengon stands experienced decreased productive tillers, plant height, stem strength, and the number and weight of grains per panicle. The IR 64 genotype decreased by 40.65% in grain weight per panicle, while the Situ Patenggang genotype experienced a 56.21% decrease.